The effect of public information on competition and R&D investment - Jim Y. Jin; Michael Tröge (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1997)
Using a simple method we show that, in contrast to the case of Bertrand and Cournot competition, better public information about demand reduces the profits of firms playing a R&D cost reduction game. Welfare increases with the precision of public information in the Cournot and cost reduction games, but not in the Bertrand game. We conclude that the provision of public information about demand in the distant future is useful and necessary in order to promote investment in R&D. Information about demand in the short term, however, should not be released. – – Mit einer einfachen Methode zeigen wir, daß im Gegensatz zum Bertrand und Cournot Wettbewerb, genauere öffentlich zugängliche Informationen über zukünftige Nachfrage die Gewinne von Firmen reduziert, die Forschungsinvestitionen zur Kostensenkung beabsichtigen. Die Wohlfahrt wird im Falle des Cournot und Forschungswettbewerbs durch bessere öffentliche Informationen erhöht, aber bei Bertrandwettbewerb verkleinert. Wir leiten daraus ab, daß die öffentliche Bereitstellung von Informationen über die zukünftige Nachfrage nützlich und notwendig ist, wohingegen Informationen die aktuelle Nachfrage betreffen nicht veröffentlicht werden sollten.
Keywords: 330